SISTEM INFORMASI PEMESANAN MAKANAN DI RUMAH MAKAN TEH EVI BERBASIS ANDROID - Pradikta Bagas Perdana; Ahmad Suryadi; Anggun Citra Dini Dwi Puspitasari (Jurnal Riset Sistem Informasi, 2024)
The purpose of this research is to help the evi tea restauran. The purpose of this research is to make it easier for ordering food to reduce the occurnece of erorrs in the manual data storage process. Shorten the time in making sales. The method used in this study is a qualitative method with the type of grounded theory.